Braided tape suture provides superior bone pull-through strength than wire suture in greater tuberosity of the humerus - Leger St-Jean, Benjamin (J Orthop, 2015)
INTRODUCTION: The purpose of this study is to compare the pull-through strength of transosseous braided tape suture with wire suture in proximal humeri bones (greater tuberosity). METHODS: A biomechanical study on eight cadaveric human specimens where two transosseous sutures were randomly applied on each specimen (anterior and posterior). Force/displacement curves were obtained for each specimen and the maximum pull-through load was noted. RESULTS: There is a significant difference in maximal pull-through strength favoring braided tape suture over wire suture. CONCLUSIONS: Transosseous braided tape suture provides almost twice the bone pull-through strength and is slightly correlated to volumetric bone mineral density.